Experimental and Clinical Evidence of Andrographis paniculata Roxb Wall Ex Nees Bhunimba A Review - Praveen Kumar A, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Experimental and Clinical Evidence of Andrographis paniculata Roxb Wall Ex Nees Bhunimba A Review